A Genome-Wide Association Study and Polygenic Risk Score Analysis of Posttraumatic Stress Disorder and Metabolic Syndrome in a South African Population - Swart, Patricia C.; van den Heuvel, Leigh L.; Lewis, Cathryn M.; Seedat, Soraya; Hemmings, Sian M. J. (Frontiers in Neuroscience, 2021)
Posttraumatic stress disorder (PTSD) is a trauma-related disorder that frequently co-occurs with metabolic syndrome (MetS). MetS, is characterized by obesity, dyslipidemia, and insulin resistance. To provide insight into these co-morbidities, we performed a genome-wide association study (GWAS) meta-analysis to identify genetic variants associated with PTSD and determined if PTSD polygenic risk scores (PRS) could predict PTSD and MetS in a South African mixed-ancestry sample. The GWAS meta-analysis of PTSD participants (n=260) and controls (n=343) revealed no SNPs of genome-wide significance. However, several independent loci as well as five SNPs in the PARK2 gene, were suggestively associated with PTSD (p < 5 x10-6). PTSD-PRS was associated with PTSD (Nagelkerke’s pseudo R2 = 0.0131, p = 0.00786), PTSD symptom severity (as measured by CAPS-5 total score (R2 = 0.00856, p = 0.0367) and PCL-5 score (R2 = 0.00737, p = 0.0353)), and MetS (Nagelkerke’s pseudo R2 = 0.00969, p = 0.0217). These findings suggest an association between PTSD and PARK2, corresponding with the largest PTSD-GWAS conducted to date. PRS analysis suggests that genetic variants associated with PTSD are also involved in the development of MetS. Overall, the results contribute to a broader goal of increasing diversity in psychiatric genetics.